108 Bilateral wilms tumours: a pictorial review. (December 2018) - Adu, J; Watson, T
Abstract : Background: Wilms tumour is the most common renal tumour in children. Synchronous bilateral disease is a rare phenomenon, manifesting in only approximately 5% of cases. Bilateral Wilms tumour (BWT) differs from Unilateral Wilm's tumour (UWT) in that it is more commonly associated with genetic syndromes which often include intrinsic renal disease, and tends to present earlier. The aim of this study is to familiarise the reader with the imaging appearances of BWT, discern how a discrete tumour can be identified in the context of nephroblastomatosis and explore the imaging features that may preclude nephron sparing surgery (NSS). Aims: We retrospectively searched the histopathology database at our tertiary referral centre over a 10 year period using the search terms 'Wilms resection' to identify cases. These cases were then cross-checked with their associated imaging on our PACS, and cases of BWT were selected for presentation. Results: 187 patients with Wilms tumours were identified. Of these, 36 patients had BWTs. Conclusion: Although BWT is rare, it is an important phenomenon to diagnose owing to the increased risk of renal insufficiency and poorer survival rates compared to unilateral Wilms tumour. NSS is critical if renal function is to be preserved. Therefore, it is crucial that radiologists recognise the key imaging features in order to facilitate prompt further management.